Impact of trauma level designation on mortality in trauma patients with sepsis: an observational study across US trauma centers - Chebl, Ralphe Bou; Diab, Razan; Siblini, Reem; Bachir, Rana; El Sayed, Mazen (Frontiers in Medicine, 2025)
BackgroundSepsis is a major complication in trauma patients, leading to increased morbidity and mortality. Given the varying resource allocation across trauma center levels, the impact of trauma center designation on sepsis-related mortality remains unclear. This study examines the association between trauma center level and sepsis outcomes in trauma patients using data from the National Trauma Data Bank (NTDB) 2017 dataset.MethodsA retrospective cohort study was conducted using the NTDB 2017 dataset at the American University of Beirut (AUB). Trauma patients who developed sepsis as a hospital complication were identified, and those meeting inclusion criteria were analyzed. Patient demographics, comorbidities, injury severity, hospital characteristics, and outcomes were compared across Level I, II, and III trauma centers. Multivariable logistic regression was performed to assess the association between trauma center designation and mortality after adjusting for confounders.ResultsA total of 1,738 patients were included. The study population had a mean age of 56.34 ± 19.54 years, with 72.9% being males and 69.2% of white race. Patients treated in a level I trauma center had a higher injury severity score (ISS ≥ 16) compared to those in other trauma center levels (62.9% vs. 54.5% vs. 22.6%, p < 0.001), and increased hospital complications, including ventilator-associated pneumonia (20% vs. 10.7% vs. 5.2%, p < 0.001). ICU and OR admissions were significantly higher in Level I and II trauma centers than in Level III (47.9% and 45.9% vs. 30.4% and 30.9%, and 24.1% vs. 13%, p < 0.001). Mortality rates were highest in Level I centers (62.4%) compared to Level II (30.8%) and Level III (6.8%), though this difference was not statistically significant after adjustment for confounders (p = 0.691). Multivariable analysis showed no significant association between trauma center designation and sepsis-related mortality when comparing Level II to Level I centers (OR = 0.785, 95% CI: 0.592–1.043; p = 0.095) and Level III to Level I centers (OR = 1.038, 95% CI: 0.454–2.372; p = 0.930).ConclusionSepsis-related mortality did not significantly differ across trauma level designation when adjusted for potential confounders. These findings highlight the importance of standardized sepsis management protocols across trauma centers as well as the importance of early sepsis recognition and intervention strategies in trauma patients.